Airborne pollen concentrations in Sierra de las Nieves National Park (southern Spain) and its allergenic potential. - De Gálvez-Montañez, Enrique; Picornell Rodríguez, Antonio; Ruiz-Mata, Rocío; Muñoz-García, Marina; Borgognone, Costanza; Recio-Criado, María Marta; Trigo-Pérez, María del Mar (My University, 2023)
Sierra de las Nieves was declared National Park in 2021. Around 100 000 people visit the park every year and a high percentage of them may suffer allergy symptoms due to the presence of some pollen types in the atmosphere. The aim of this study was to determine the allergenic potential of the concentrations registered in the atmosphere of Sierra de las Nieves National Park as well as the seasonality of different pollen types. Airborne pollen was sampled by means of a Hirst-type volumetric pollen trap installed in “Las Conejeras” recreational area. In this study, data of the year 2022 were considered. Pollen samples were mounted and counted following the methodology proposed by the Spanish Aerobiology Network. Data were managed by means of the AeRobiology package, implemented in R software. Spearman correlations test between daily pollen concentrations and the main meteorological parameters were performed. Airborne pollen was detected during almost the whole year, with the highest concentrations being reached during the period April-June (89.19% of the total annual pollen integral). The pollen type with the highest number of days with concentrations of high allergenic potential was Quercus (25 days), followed by Castanea and Poaceae (8 days), the period with the highest risk for allergy sufferers being April-July. High temperatures favour pollen release, increasing the airborne pollen concentrations, but precipitation and high relative humidity favour pollen precipitation, reducing airborne pollen concentrations. Wind dynamics play different roles depending on the pollen type considered, due to the heterogeneous distribution of the pollen emission sources. Allergy sufferers should consider the pollination period of the pollen types which they are allergic to when planning their visits to the National Park, especially on days with high temperatures and low relative humidity, meteorological conditions that tend to increase pollen concentrations.
Keywords: Alergia; Polen - Dispersión - Factores climáticos; Aerobiología; Sierra de las Nieves